Ethics without IRB, is that possible? the case study of participatory sessions with ASD children in Mexico - Escobedo Bravo, Lizbeth Olivia; Cibrian, Franceli L.; Tentori, Mónica (My University, 2023)
Research involving participatory design with children necessarily implies a careful review of the research methods to ensure participants’ safety; However, in Latin America may be different than in the Global North countries. Over the past 13 years, we have partnered with a school-clinic in Mexico that specializes in assisting children with autism. During this time, we designed, developed, and assessed UbiComp technology to assist in various stages of a child's therapy cycle. We have been collaborating with the school-stakeholders such as children and young adults with autism, parents, teachers, psychologists, and therapists, including them in all the phases of the projects. In this paper, we reflect on our experiences at this school-clinic, discussing the formality and ethics when conducting research. We close by presenting the implications we have learned while conducting research with this population.
UbiCompt
Keywords: ASD; Children; Ethics; Campus Tijuana